Teologi Pembebasan dalam Karya-karya K.H Abdurrahman Wahid : Analisis Buku Islamku, Islam Anda, Islam Kita - Addzaky, Khoirul Umam; Hasanah, Uswatun; Hasanah, Ida Faridatul; Ari, Muhammad Asy'ari (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
The writing on liberation theology, which originally developed in the Latin American Christian tradition, has found its resonance in contemporary Islamic thought. K.H. Abdurrahman Wahid is one of the Indonesian Muslim figures who made significant contributions to the development of this discourse. This research aims to analyze the manifestation of liberation theology in Gus Dur's thought as well as identify its distinctive characteristics through the study of the book “Islamku, Islam Anda, Islam Kita” with a qualitative approach and content analysis method. The main findings of the study reveal three distinctive characteristics of Gus Dur's liberation theology: an innovative synthesis of traditional fiqh with modern social justice principles, particularly in his advocacy of minority rights; the reinterpretation of religious texts to challenge authoritarian interpretations, reflected in his defense of religious freedom and democratic values; and the development of an Indonesian model of Islamic pluralism that emphasizes grassroots empowerment. The practical significance of the findings provides a theoretical foundation for interfaith dialogue, minority protection, and democratic reform in contemporary Indonesia. The unique contribution of this research lies in documenting how Gus Dur successfully bridged the gap between Islamic traditionalism and modern progressive thought, creating an Indonesian approach to liberation theology that remains relevant to address contemporary social challenges, and providing a foundation for understanding how religious thought can be mobilized for social transformation in pluralistic societies.